The implementation of principal’s supervisory style in improving teachers’ job satisfaction at SMK Negeri 1 Gowa - Ayuashari, Andi Ratu; Ansar , Ahlun; Jannah , Miftahul (Priviet Social Sciences Journal, 2025)
Principals play a strategic role in improving the quality of teaching and teacher performance through supervisory practices. This study aims to describe the implementation of the principal’s supervisory style in enhancing teachers’ job satisfaction at SMK Negeri 1 Gowa. This research employed a descriptive qualitative approach, with data collected through observations, in-depth interviews, and documentation. The participants included the principal, six vice principals, senior teachers, and teachers who were the subjects of supervision. The findings indicate that the principal implemented an integrated, structured, and participatory supervisory style. This approach can be categorized as guided leadership, which emphasizes mentoring, support, and teacher involvement in decision-making. The implementation of supervision was not merely focused on administrative evaluation but functioned as a medium of empowerment through constructive feedback, continuous mentoring, and collective reflection. Teachers reported feeling valued and supported, which positively influenced their motivation, professionalism, work discipline, teaching readiness, and overall job satisfaction. Furthermore, the supervisory practices were closely linked to teacher performance appraisal (PKG) and work target assessments (SKP), contributing to the strengthening of career development and performance-based recognition. These results highlight that a humanistic, educational, and participatory supervisory style fosters a positive school climate, promotes collaboration, and enhances the quality of teaching and learning in vocational education settings.